Early surprise: managing natal tooth in a 22-day-old infant - Singh, Vritika; Sharma, Reema; Jain, Shantanu; Marwah, Nikhil; Sharma , Vipul (International Journal of Contemporary Pediatrics, 2024)
The presence of teeth at birth or earlier than expected is a rare phenomenon and can evoke a variety of reactions. Natal teeth are those present at birth, while neonatal teeth appear within the first 30 days after birth, constituting an unusual and rare occurrence. This case report describes the management of a 22-day-old female infant with presence of an excessively mobile tooth in the lower jaw since birth, causing breastfeeding difficulties. The tooth appeared whitish opaque in colour, with grade II mobility. Crown size, shape, and appearance were similar to normal teeth. Due to the association of natal teeth with breastfeeding discomfort, extraction was recommended. No vitamin K prophylaxis was administered as the baby had achieved normal safe levels. Topical anesthesia was applied, and the tooth was extracted using primary anterior forceps. Hemostasis was achieved with sterile cotton gauze, and the patient was discharged post-extraction.